Teori Vygotsky: Kajian bibliometrik penelitian cooperative learning di sekolah dasar (1987-2023) - Muhammad, Ilham; Darmayanti, Rani; Sugianto, Rahmad; Choirudin (Bulletin of Educational Management and Innovation, 2023)
Vygotsky's theory and its application in cooperative learning in primary schools have significant importance in the educational context. Cooperative learning is student-centered learning with the hope that students will find it easier to find and understand concepts from material or a problem by discussing it with their group mates. The aim of this study is to examine the research landscape related to cooperative learning of elementary school students from 1987 to 2023. The method used is descriptive bibliometric analysis. Source of data obtained from the Scopus database. This study used a panel method that refers to the PRISM (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Based on the initial search, 163 articles related to cooperative learning were obtained, The result  show that The new themes in this research are problem solving, game-based learning, collaborative learning, and learning. Cooperative learning keywords are not directly connected with social behavior, human, gender, controlled study and behavior disorder. The focus of research in this field is, 1) teaching, problem solving, and e-learning; 2) human, gender, and student.